“Once it’s your sister, they think it’s in the bloodline”: impact of HIV/aids- related stigma in Ghana - Asiedu, Gladys Barkey (Kansas State University, 2010)
The purpose of this study was to conduct a phenomenological inquiry into the impact HIV/AIDS-related stigma has on People Living with HIV/AIDS (PLHA) and their family members in Ghana and the overall relationship family members have with PLHA. The study explored the concept of stigma in the Ghanaian context, ways in which it is expressed, factors influencing HIV- related stigma and its consequences on both PLHA and their family members. Strategies that PLHA and their family members consider for effective HIV- related stigma prevention were also explored. The study further explored some of the gender- biased nature of HIV- related stigma in Ghana. Data was gathered qualitatively through interviews with five PLHA and their discordant family members. Interviews were transcribed and translated into English, coded and analyzed. After inductively establishing themes and categories, final confirmatory analysis was deductively established, by using the Bronfenbrenner’s ecological model and Symbolic interaction theory to affirm the authenticity and appropriateness of the inductive content analysis. The study found that HIV- related stigma begins with serostatus disclosure. Stigma is manifested in myriad contexts including the family, community, healthcare institutions and gender. The major factors influencing stigma are insufficient knowledge of HIV transmission, fear and misconception of HIV created by the media, cultural and religious factors as well as poverty. Family members experienced similar stigma as PLHA, such as loss of jobs, loss of social network, loss of identity and self stigma. However extreme impacts such as suicidal thoughts were only experienced by PLHA. The impact of HIV- related stigma is worst for women because of beliefs and values relating to gender- role expectations. While women accept and support their husbands when they have HIV/AIDS, women are often neglected and abandoned by their husbands. To address this stigma, participants suggested house to house education, financial support from the government, revision of educational content especially discontinuation of negative images of HIV/AIDS used by the media. Implications for this study in the areas of research, practice and policy are provided.
Keywords: HIV/AIDS; HIV/AIDS related stigma and discrimination; Gender and HIV/AIDS; Stigma and discrimination; People living with HIV/AIDS; women and AIDS related stigma; Black Studies (0325); Education, Social Sciences (0534); History, African (0331); Psychology, Behavioral (0384); Social Work (0452); Sociology, Individual and Family Studies (0628); Women's Studies (0453)